THE INFLUENCE OF SKYPE TOWARDS STUDENTS’ WRITING SKILL - Yuski Iskandar; Sayid Ma’rifatulloh (Teaching English as Foreign Language, Literature and Linguistics, 2021)
One of the main skill in learning English as second language is writing. Learning writing is necessarily important nowadays, not only for education purposes but also for occupation purposes as well. However, most of the students feel bored in writing; one of the reasons is because the teaching learning process still uses conventional method. Thereby, it seems that writing is difficult and boring because the students score in writing is low. Therefore, the researcher uses Skype as the media in teaching writing as an alternative solution for this problem. The study aim is to find if there is any significant influence of using Skype towards students’ writing skill especially in writing descriptive text. The result of this study showed that there is a significant influence of using Skype towards students’ writing skill.